Lower adenoma detection rate in anesthesia assisted colonoscopy: a retrospective study - Cai, Chang; Xu, Zhihua; Ye, Bin (Frontiers in Oncology, 2025)
ObjectivesAs anesthesia assisted (AA) colonoscopy becomes increasingly popular, there has been concern about its impact on the quality of colonoscopy examinations. We aimed to clarify the impact of anesthesia assistance on the adenoma detection rate (ADR) and non-adenomatous polyp detection rate (PDR) of colonoscopy.MethodsWe collected data from patients undergoing colonoscopy throughout the year 2023 at our institution, with a total of 16,465 cases identified for potential analysis. After using propensity score matching (PSM) to minimize the influence of other variables on the study outcomes, there were 6,094 cases remaining for analysis in both the AA group and non-AA group, respectively. Then, we compared the ADR and PDR between the two groups and analyzed the colon location and size of adenomas or polyps found in different groups.ResultsThe ADR in the non-AA group (36.94%) was significantly higher than that in the AA group (26.40%) (p<0.0001), while there was no statistically significant difference in the PDR between the two groups. AA could also affect the probability of discovering adenomas or polyps in some colon segments, but had no significant effect on the size of the discovered adenomas or polyps. In addition, there were more significant advantages of ADR in the non-AA group among the more experienced endoscopists’ cohort.ConclusionsNon-AA colonoscopy had a higher ADR, suggesting that while AA may potentially reduce patient stress responses to some extent, it confers few benefits in terms of adenoma detection.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=232248.